Periviable Premature Rupture of Membranes—Maternal and Neonatal Risks: A Systematic Review and Meta-analysis - Saucedo, Alexander M.; Calvert, Chase; Chiem, Adrian; Groves, Alan; Ghartey, Kobina; Cahill, Alison G.; Harper, Lorie M. (American Journal of Perinatology, 2024)
Objective Periviable premature rupture of membranes (PROM) counseling should describe maternal and neonatal outcomes associated with both immediate delivery and expectant management. Unfortunately, most published data focuses on neonatal outcomes and maternal risk estimates vary widely. We performed a meta-analysis to describe outcomes associated with expectant management compared with immediate delivery of periviable PROM.Study Design We performed a search on PubMed, MEDLINE, Web of Science, PROSPERO, Cochrane library, and ClinicalTrials.gov utilizing a combination of key terms. Published clinical trials and observational cohorts were included if published after 2000. Publications were selected if they included maternal and/or neonatal outcomes for both expectant management and immediate delivery. Gestational age range was limited from 14 to 25 weeks. The primary outcome was maternal sepsis. Secondary outcomes included chorioamnionitis, hemorrhage, laparotomy, and neonatal survival. Pooled risk differences (RDs) were calculated for each outcome using a random-effects model. Publication bias was assessed using funnel plots and Harbord test.Results A total of 2,550 studies were screened. After removal of duplicates and filtering by abstract, 44 manuscripts were reviewed. A total of five publications met inclusion for analysis: four retrospective and one prospective. Overall, 364 (68.0%) women underwent expectant management and 171 (32.0%) underwent immediate delivery. Maternal sepsis was significantly more frequent in the expectant group (RD, 4%; 95% confidence interval, 2–7%) as was chorioamnionitis (RD: 30%; p < 0.01) and any laparotomy (RD: 28%; p < 0.01). Neonatal survival in the expectant group was 39% compared with 0% in the immediate group (p < 0.01).Conclusion Women who undergo expectant management following periviable rupture of membranes experience significantly increased risks of sepsis, chorioamnionitis, and laparotomy. Overall, 39% of neonates survive to discharge. Knowledge of these risks is critical to counseling patients with this diagnosis.Key Points
Keywords: periviable; previable; midtrimester; second trimester; rupture of membranes; expectant management; immediate delivery; termination